The Sydney multicentre study of Parkinson's disease: progression and mortality at 10 years. Issue 3 (1st September 1999) - Hely, Mariese A; Morris, John G L; Traficante, Robert; Reid, Wayne G J; O'Sullivan, Dudley J; Williamson, Peter M
Abstract : OBJECTIVES: To report on a 10 year follow up of patients with idiopathic Parkinson's disease, particularly with respect to mortality and the effect of early treatment with bromocriptine. METHODS: The patients are from the 149 new patients recruited for a double blind, randomised study of low dose levodopa-carbidopa versus low dose bromocriptine. Patients were examined neurologically at least yearly. Neuropsychological examinations were performed at 0, 3, 5, and 10 years. Mortality and cause of death in these patients were compared with the Australian population using standardised mortality ratios (SMRs). Mortality and disease progression were compared by sex and treatment group. Predictors of death within 10 years, nursing home admission, and progression in Columbia score of ⩾20 points were examined by logistic regression analysis. RESULTS: Thirteen patients were excluded as having atypical Parkinsonism and six were lost to follow up. All available patients have been followed up for 10 years. Fifty patients (38%) were dead by 10 years and 63 by the last follow up. The SMR was 1.58 for all patients (p<0.001). There was no significant difference in SMRs between the sexes. The mean duration of disease until death was 9.1 years. Parkinson's disease was thought to have contributed substantially to the death of 30 patients. The most common cause of death was pneumonia. Women progressed at a similar rate to men until 8 years, when the severity of their disease as measured by Hoehn and Yahr stage became greater (p<0.05). Older age of onset correlated with increased risk of death but the SMR was increased even in those aged <70 years (SMR 1.80, p=0.03). Early use of bromocriptine did not reduce mortality or slow progression of disease. One quarter of all patients had been admitted to nursing homes by 10 years. Only four patients were still employed. CONCLUSIONS: Mortality in Parkinson's disease remains increased despite low dose levodopa-carbidopa therapy and no additional benefit was gained from early use of bromocriptine. Duration of disease was similar to that in the era before levodopa.